Pengembangan Petunjuk Praktikum Biologi Berbasis Guide Inquiry Materi Interaksi Makhluk Hidup Dengan Lingkungan - Pujo Ary Prasetyo Wati; Hernik Pujiastutik (Universitas Sebelas Maret, 2018)
The purpose of this study is to produce guided practicum biology guide guide-based on the material interaction of living things with the environment. This research is a research development of practice manual by using R & D method (Research and Development) and use 3D development model from 4-D model (Four D). 3D development model consists of 3 main stages: Define (Define), Design (Design), and Develop (Development). The research was conducted at SMP N 1 Kerek, Tuban. Subjects in this research are 2 lecturers and 1 teacher of Biology as validator and 32 students of class VII SMP N 1 Kerek. result of validity test from material expert and media expert obtained average score validity equal to 84,96% with category very valid. Based on practicability test of practice manual obtained result of 90,62% with very practical category.The result of the effectiveness test result of students learning completeness with a score of 87,50% with very completeness category, the result of student responses average list of achievement of 84,37%. While based on the observation of student activity shows the average value of each aspect in accordance with the criteria values specified in the effective category. It can be conclude that guide practicum biology in classification is valid, practical, and effective.